The Old Lady Visits Your Backyard: A Tale of Morals and Markets - Frey, Bruno S.; Oberholzer-Gee, Felix; Eichenberger, Reiner (Journal of Political Economy, 1996)
Local opposition to many projects makes it increasingly difficult to find sites for socially desirable facilities. As has been widely documented, compensation for local disamenities does not increase the level of support. An empirical analysis of the Swiss search for a nuclear waste repository even reveals decreased acceptance due to the rejection of bribes and the crowding-out of public spirit. However, a "compensation cycle" may be exploited to finally win the support of host communities. As siting issues are decided in the realm of politics, an economic theory of compensation must focus on the interplay between morals and markets.